Examining future park recreation activities and barriers relative to societal trends. Issue 4 (8th August 2019) - Zanon, Dino; Curtis, Jim; Lockstone-Binney, Leonie; Hall, John
ABSTRACT: This study empirically examines how future park recreation is related to enduring societal trends. An online panel of 927 participants was surveyed regarding anticipated park recreation participation in ten years' time in terms of intended park activities and expected barriers, adapted from the Theory of Planned Behaviour, the Recreation Experience Preference scales and Leisure Constraints theory. Anticipated changes were then linked by participants to the particular societal trends impacting them. The results suggest increased activities are expected from the 'health awareness' and 'independence and convenience' societal trends, while increased barriers are expected from 'climate change', 'perceived safety' and 'population and urban growth'. Overall, the percentage of participants reporting future increased activities at parks is equal to those reporting future barriers; which suggests potentially that there will be no net participation change over time. The management implications, limitations and potential future research agenda stemming from the study are discussed.